Antibiotic Sensitivity Profile of Bacteria in Open Wound Infections in Orthopedic Patients at Kraton Regional General Hospital, Pekalongan Regency, February 2025 - Aditya Firmansyah; Mulia Susanti (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background & Objective: Open wound infections in orthopedic patients are infections caused by accidental wounds that have been contaminated with bacteria. Bacteria enter through abrasions or grazes caused by skin rubbing against rough surfaces such as asphalt. Based on medical records from Kraton Regional General Hospital in Pekalongan Regency in 2024, there were a total of 967 cases of patients due to accidents, and in February 2025, there were 5 patients. This study aims to determine the bacterial species and antibiotic sensitivity of bacterial isolates found in open wound infections in orthopedic patients at Kraton Regional General Hospital in Pekalongan Regency. Method: This study used a descriptive research method to identify bacteria and test the antibiotic sensitivity of bacteria in open wound infections in orthopedic patients at Kraton Regional General Hospital, Pekalongan Regency. Result: The results of the study showed that 40% of Escherichia coli and 40% of Staphylococcus aureus were found. Escherichia coli from sample one was resistant to Ampicillin and Ceftriaxone and intermediate to Cefotaxime. Escherichia coli from sample four was sensitive to Ampicillin, Ceftriaxone, and Cefotaxime. Staphylococcus aureus from samples three and four was resistant to Ampicillin and Ceftriaxone and sensitive to Cefotaxime. Conclusion: There are bacteria causing open wound infections in orthopedic patients at Kraton Regional General Hospital, Pekalongan Regency, namely Escherichia coli 40% and Staphylococcus aureus 40%. The percentage of antibiotic sensitivity tests was Ampicillin 50%, Ceftriaxone 50%, and Cefotaxime 50%.